A STUDY OF THE MEANING AND CHARACTERISTICS OF SERVANT LEADERSHIP AMONG REGISTERED NURSES AT KING CHULALONGKORN MEMORIAL HOSPITAL, THAI RED CROSS SOCIETY: A QUALITATIVE STUDY - Sripinkaew, Pongwit; Bovornusvakool, Witsinee (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2025)
This study was a qualitative research project aimed at studying the meaning and characteristics of servant leadership among registered nurses at King Chulalongkorn Memorial Hospital, Thai Red Cross Society, through focus group discussions. The Informants were 20 nurse executives and registered nurses who had completed nursing management or executive leadership training programs and had at least 10 years of work experience. Research instruments included the researcher, a personal information questionnaire, and a semi-structured interview guide on servant leadership among registered nurses at King Chulalongkorn Memorial Hospital. These tools were validated by 3 experts, yielding a 90% agreement rate. Data were analyzed using thematic analysis, and trustworthiness and data saturation were verified through triangulation methods. The research findings revealed three major themes of servant leadership among registered nurses at King Chulalongkorn Memorial Hospital: 1) The meaning of servant leadership involves being a good role model, providing quality service that adds value to the nursing profession, and engaging in self-development that leads to organizational development; 2) There are 16 identified characteristics of servant leadership; 3) Nurturing servant leadership begins with the individual, while the organization must also provide support and opportunities for growth. The data obtained from the analysis also highlighted the beliefs, experiences, thoughts, and behaviors of the key informants related to servant leadership, which contribute to the development of appropriate servant leadership measurement tools tailored to registered nurses and aligned with the organizational context of King Chulalongkorn Memorial Hospital, Thai Red Cross Society. This scale can serve as a guideline for the further development of servant leadership.